Eritrea : Education and Training Sector Note - World Bank (Washington, DC, 2013)
This sector note aims to assist the Government, and the Ministry of Education in developing a joint strategy, and action plan for the education, and training sector, and to improve coordination of donor inputs related to this strategy. The note provides an analysis of major issues, achievements, and bottlenecks in the current system, and an overview of key priorities, and recommendations for actions to improve the performance of the sector. As well, it provides a background document for discussions with other education stakeholders, and international donors. Within the country's socioeconomic context, the note reviews the priority challenges the country faces, namely to improve access to, and equity, and quality of education. School mapping will be needed to establish the provision of educational services, as well as a strategy document for providing services to the nomadic population, to raise the net enrollment ratio. The causes, and effects of repetition, and drop-outs should be further analyzed, which includes teacher skills, and attitudes. Solutions could include the automatic promotion for the primary level, phasing out late-age-entry into primary and over-age students, and, providing the alternative of distance learning education. Teacher training should be significantly improved, through teacher certification, intensified in-service support, and English language skills. The note further emphasizes on strengthening, and expanding institutional capacity, and creating a sustainable, equitable financing system.